An An Innovative SETS-Based Problem-Based Learning Model to Improve Critical Thinking and Cognitive Outcomes in Biology - Fitria Nurhafisah; Bea Hana Siswati; Inggrit Aulya Hartono; Gita Eka Ayu Saputri (Universitas Ahmad Dahlan, 2025)
In order to enhance students’ cognitive learning outcomes and critical thinking abilities in Biology classes, this study implements a SETS-based Problem-Based Learning (PBL) model. The purpose of this study was to determine the effect of the SETS-based Problem-Based Learning (PBL) model on the cognitive learning outcomes and critical thinking skills of Grade X Biology students in industrial agricultural settings. A quasi-experimental design was applied, consisting of a control class and an experimental class that was taught using the SETS-based PBL approach. Students’ cognitive learning outcomes were evaluated through ANCOVA, while their critical thinking skills were analyzed using the non-parametric Mann–Whitney test. The ANCOVA results revealed a significance value of 0.041 (<0.05), indicating a significant improvement in students’ cognitive learning outcomes, whereas the Mann–Whitney test produced a significance value of 0.002 (<0.05), confirming a significant enhancement in critical thinking skills. Based on these findings, it can be concluded that the implementation of the SETS-based PBL model effectively improves both cognitive learning outcomes and critical thinking skills of Grade X students in industrial agricultural areas.